THE CHOICE OF THE METHOD OF ENDOSCOPIC STENTING IN PATIENTS WITH UNRESECTABLE ADENOCARCINOMA OF THE PANCREATIC HEAD - A. V. Shabunin; M. M. Tavobilov; S. S. Lebedev; I. Yu. Korzheva; A. A. Karpov; A. V. Lantsynova (Сибирский онкологический журнал)
The purpose of the study was to comparatively assess the endoscopic plastic or nitinol stenting in patients with unresectable adenocarcinoma of the pancreatic head, who subsequently received systemic chemotherapy.Material and Methods. Between 2014 and 2018, 64 patients underwent retrograde stenting followed by chemotherapy. All patients were divided into 2 groups. Group I consisted of 21 patients, who underwent nitinol stent implantation. Group II comprised 43 patients, who underwent plastic stent implantation.Results. The technical success was 91.3 % in group I and 93.5 % in group II (р=0.324); clinical success was 95.2 % in group I and 90.6 % in group II (р=0.218). Complications according to the Clavien–Dindo classification in group I patients: Grade II in 2 (9.5 %), Grade III in 1 (4.5 %), and Grade IV 2 in (9.5 %). In group II patients, these complications were as follows: Grade II in 4 (9.3 %), Grade III in 4 (9.3 %), and Grade IV in 1 (2.3 %). The median duration of chemotherapy was 127.3 days. Stent dysfunction was observed in 5 (23.8 %) patients of group I and in 24 (55.8 %) patients of group II (р=0.026). The median time of stent patency was 108 ± 5.2 days in group I and 64 ± 4.3 days in group II (р=0.034). In group I patients, the median survival time was 100 days in 5 patients, 120 days in 9 patients, and 150 days in 5 patients. Two patients are alive. In group II patients, the median survival time was 100 days in 10, 120 days in 16, and 150 days in 13. Five patients are alive.Conclusion. Based on the results obtained, it is advisable to recommend the use of nitinol stents for resolving obstructive jaundice in patients with unresectable ductal adenocarcinoma of the pancreatic head, who are scheduled to undergo chemotherapy.